2016
DOI: 10.3762/bjnano.7.147
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor magnetic hyperthermia induced by RGD-functionalized Fe3O4 nanoparticles, in an experimental model of colorectal liver metastases

Abstract: This work reports important advances in the study of magnetic nanoparticles (MNPs) related to their application in different research fields such as magnetic hyperthermia. Nanotherapy based on targeted nanoparticles could become an attractive alternative to conventional oncologic treatments as it allows a local heating in tumoral surroundings without damage to healthy tissue. RGD-peptide-conjugated MNPs have been designed to specifically target αVβ3 receptor-expressing cancer cells, being bound the RGD peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 61 publications
1
31
0
2
Order By: Relevance
“…Heterotopic implantation of cancer cells is also a validated model to induce tumour development in laboratory animals, particularly in rats and mice. Cells may be implanted directly into the liver parenchyma, via subcapsular injection, and this approach achieves a high tumour development rate: up to 60-70% of the injected animals (37)(38)(39). But this model is not appropriate for our purposes because it only allows the development of single well-de ned and localized tumour implants, and also it lacks the process of tumour cell dissemination through the vascular tree and subsequent extravasation to produce metastatic disease in the liver (40).…”
Section: Experimental Tumour Induction Modelmentioning
confidence: 99%
“…Heterotopic implantation of cancer cells is also a validated model to induce tumour development in laboratory animals, particularly in rats and mice. Cells may be implanted directly into the liver parenchyma, via subcapsular injection, and this approach achieves a high tumour development rate: up to 60-70% of the injected animals (37)(38)(39). But this model is not appropriate for our purposes because it only allows the development of single well-de ned and localized tumour implants, and also it lacks the process of tumour cell dissemination through the vascular tree and subsequent extravasation to produce metastatic disease in the liver (40).…”
Section: Experimental Tumour Induction Modelmentioning
confidence: 99%
“…In the early symptom liver metastasis mouse model of colorectal cancer, the oleic acid-wrapped ferrite RGF polypeptide complex (Fe 3 O 4 @PMAO_RGD) was injected into the hepatic artery to bind with the surface αVβ3 receptor of the tumor cell and then MFH was conducted under the action of AMF. It was found that the activity of colorectal cancer liver metastasis tumor cells was remarkably lowered [70]. Combined therapy of MFH with targeted chemotherapy and (or) gene therapy had shown a promising application prospect in the diagnosis and treatment for tumor.…”
Section: Tumor-targeted Thermotherapy Of Magnetic Nanometer Materialsmentioning
confidence: 99%
“…Nanopartículas magnéticas (NPMs) de ferrita de zinc (Arteaga-Cardona et al, 2017) Nanopartículas de ferrita de níquel revestidas con polietilenglicol (PEG) (Iqbal, Bae, Rhee & Hong, 2016) Nanopartículas de maghemita (Múzquiz-Ramos, Guerrero-Chávez, Macías-Martínez, López-Badillo & García-Cerda, 2015) Nanopartículas de ferrita de Mn 2+ dopado Mg 0.5 Zn 0.5 -xMn x Fe 2 O 4 (x = 0, 0.125, 0.250, 0.375, 0.500) (Sharma et al, 2017) Nanopartículas de ferrita de cobalto (Yadavalli, Jain, Chandrasekharan & Chennakesavulu, 2016) Microemulsión Nanopartículas magnéticas recubiertas con ácido oleico (NPMsOA) cargadas con poli (metacrilato) (Feuser et al, 2015) Nanopartículas de sílice modificadas orgánicamente (ormosil) (Nagesetti & McGoron, 2016) Magnetita superparamagnética (Fe 3 O 4 ) (Ramesh, Ponnusamy & Muthamizhchelvan, 2011) Nanopartículas de perovskita a base de manganeso (Soleymani & Edrissi, 2016) Descomposición térmica Ferrofluído de Fe 3 O 4 funcionalizado con péptidos RGD (Arriortua et al, 2016) Nanocristales de óxido de hierro (Bear et al, 2014) Nanopartículas de ferrita de cobalto (Cotica et al, 2014) Nanopartículas de ferrita dispersables en agua superparamagnéticas (MFe 2 O 4 ) (Sabale, Jadhav & Yu, 2017) Nanopartículas de ferrita de níquel (Stefanou et al, 2014) Nanopartículas de magnetita (Fe 3 O 4 ) (Xiao et al, 2015) Sonoquímica Nanocompuestos magnéticos PET / Fe 3 O 4 , CA, AS (Mallakpour & Javadpour, 2018) Ferrofluido de hematita/magnetita (Zayed, Ahmed, Imam, & El Sherbiny, 2016a, 2016bZayed, Imam, Ahmed, & El Sherbiny, 2017) Técnica de Massart…”
Section: Método De Síntesis Materials Utilizado Autoresunclassified